2015
DOI: 10.1097/jsa.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

DeNovo NT Particulated Juvenile Cartilage Implant

Abstract: Biological repair of focal chondral defects represents a significant clinical challenge as cartilage lacks intrinsic healing ability. Although it can be difficult to measure the objective success of cartilage repair techniques, the primary objective is symptom relief leading to less pain and improved function for the patient. Likely, the most important key to success is proper clinical indications. Second to this, the type of cartilage treatment utilized should be based on lesion location, size, depth, and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…For CD81 (cluster of differentiation 81) and Mesenchymal stem cell (MSC) markers, CD90 (also known as Thy-1) and CD44 (a receptor for hyaluronic acid) were more than 95% positive for all lots. We have reported that these markers are expressed in both adult chondrocyte sheets, which exhibited effectiveness in a previous clinical study and PD sheets [10]. There was almost no significant difference in the expression of these cell surface markers between the lots (see Figure 1e).…”
Section: Effect Of Pd Sheets On Hyaline Cartilage Regenerationmentioning
confidence: 75%
See 2 more Smart Citations
“…For CD81 (cluster of differentiation 81) and Mesenchymal stem cell (MSC) markers, CD90 (also known as Thy-1) and CD44 (a receptor for hyaluronic acid) were more than 95% positive for all lots. We have reported that these markers are expressed in both adult chondrocyte sheets, which exhibited effectiveness in a previous clinical study and PD sheets [10]. There was almost no significant difference in the expression of these cell surface markers between the lots (see Figure 1e).…”
Section: Effect Of Pd Sheets On Hyaline Cartilage Regenerationmentioning
confidence: 75%
“…We have demonstrated the efficacy of chondrocyte sheet transplantation in allogeneic settings in rats, rabbits, and minipigs without immunosuppression [5][6][7][8]. Additionally, many allogeneic osteochondral transplantations in histoincompatibile patients have been conducted safely [10,45,46]. However, the influence of histoincompatiblility on efficacy of PD sheet transplantation is still unknown, as we are currently evaluating the immune response in the PD sheet transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cells. [2][3][4] Allogeneic juvenile cartilage (DeNovo NT, Zimmer, Warsaw [IN], USA) and allogeneic juvenile 3-dimensional neocartilage (RavaFlex/DeNovo ET, ISTO Tec, St Louis [MO], USA) have been used for cartilage repair, [5][6][7] but their immune response remains unclear. The use of autologous chondrocyte implantation (ACI) is limited by the waiting period for cell culture and low cell number and density for large defects or subsequent surgeries.…”
mentioning
confidence: 99%
“…Current approaches and trials are exploiting novel intraoperative point of care cell and tissue processing. Technologies such as Carti‐One™ (Orteq® LTD, United Kingdom) or minced cartilage approaches allow for a single staged approach with scope for autologous tissue inserted onto a carrier to be delivered arthroscopically for improved repair of cartilage defects . Cartilage autograft implantation system (CAIS, DePuy Synthes, Mitek Sports Medicine) is a simplified one step procedure which eliminates technical difficulties and high costs associated with conventional ACI …”
Section: Evolution and Progress In Cartilage And Disc Repair Strategiesmentioning
confidence: 99%